The Effect of Tri-Core Breastfeeding Models on Mother’s Willingness to Breastfeed in COVID-19 Era - Kadek Widiantari; Made Pradnyawati Chania; Ni Nyoman Deni Witari (Babali Publisher, 2023)
Introduction: Failure to give exclusive breastfeeding is one of the problems that is commonly found in postpartum mothers, especially in primiparas. For primiparas, being a mother is a new role that is quite difficult because it requires an adaptation process on how to split time between taking care of the baby, husband, and personal needs. Tri-Core Breastfeeding Models is a practice guideline in the form of health promotion to mothers in breastfeeding, which can improve maternal and child health, which consists of three parts: Lactation Education, Self Confidence, and Lactation Support. Method: The design of this study was a quasi-experimental design with a post-test only control group design. The total sample was 30 respondents divided into two groups (control and treatment) with 15 respondents in each group. The sampling technique used was purposive sampling. The data collection tool used is the Infant Feeding Intention (IFI) questionnaire. T-test was used for bivariate data analysis. Results: The results show that the mean score of the mothers’ willingness to breastfeed in the group that was given the Tri-Core Breastfeeding Models (14.6) was higher than the group that was not given the Tri-core Breastfeeding Models (6.7) (p-value = 0.001) Conclusion: There was a significant effect of the application of Tri-Core Breastfeeding Models on the Mother’s Willingness to Breastfeed in the COVID-19 Era.